Can “Integrated Learning” with English support science education? A case study in Portugal - Piacentini, Valentina (2022)
Content and Language Integrated Learning (CLIL) is an approach used in different countries for learning foreign languages (FL) during non-language classes. Studies suggest that teaching methodologies aware of (verbal) language–such as CLIL–and other science modes (operational, symbolic, visual, etc.) can be beneficial for learning science. Within this PhD research, we aimed to understand science education practices and the influence of English (as a FL) on CLIL science teaching/learning. We designed a qualitative case study in a Portuguese school and gathered information through different methods. We found that, because English is present, a science teacher may become more open to the students’ (language) learning difficulties and to changing strategies/resources. Besides promoting FL proficiency, CLIL could represent a language-aware approach for enhancing science teaching/learning. This contributes to studies on CLIL and science education with a language focus and opens a reflection on teacher practices/education for the learning of science.